Modeling and Prediction of the Mortality Trend due to Accidents in Golestan Province Based on the Lee-carter Model - Alireza Heidari; Mohammad Javad Kabir; Sajad khodabandelu; Nahid Jafari; Zahra Khatirnamani; Masoumeh Gholami (Mazandaran University of Medical Sciences, 2022)
Introduction and purpose: Accidents are one of the main causes of death that impose a great socioeconomic burden on society. This study aimed to model and predict the trend of mortality due to accidents in Golestan province, Iran, from 2011 to 2020. Methods: The study was a secondary analysis based on the available data. The required information was obtained from the statistics unit of the Health Department of Golestan University of Medical Sciences (Gorgan, Iran) and was cleaned after being entered into the Microsoft Office Excel software (2016). Afterward, all the steps of analysis and fitting of the Lee-Carter model were performed using the Demography (version 18/1) and StMoMo packages in the R/3/62 software. Results: The death rate due to accidents in 2011 was 0.51 in the total population, 0.23 in women, and 0.78 in men per 1,000 population. It is predicted that in 2028, the age group of over 80 will reach 2.17 in the total population, 2.12 in men, and 1.77 in women (per 1,000 population). Both men and women over 50 years of age had the highest increase in deaths from accidents. Conclusion: Based on the findings of the study, the trend of deaths due to accidents in Golestan province is upward. Therefore, it is necessary to plan to reduce accidents, and in this regard, specific strategies should be formulated and implemented by explaining the role of all stakeholders.